Walking the Tight Rope: Balancing the Property Rights of Individuals with the Right to Housing of Informal Settlers - Matu, Doris (Strathmore Law Review, 2016)
The Constitution of Kenya, 2010 provides for the right to property in Article 40. Further, in Article 43 (1)(b), it provides for the right to accessible and adequate housing. The purpose of this article is to show the conflict that arises between the right to property for owners of land and the right to housing of the informal settlers living on these privately owned lands. The main objective is to investigate the concept of illegal forced evictions and the legal framework that surrounds the practices that render such evictions against the principle of human dignity and the right to accessible and adequate housing in the context of informal settlements. The 2010 Constitution states that every person shall enjoy the rights and fundamental freedoms in the Bill of Rights to the greatest extent consistent with the nature of the right or fundamental freedom. This renders important the concern that arises when persons informally settle onto land that they have no legal title to; what is the balance to be maintained between property rights and housing rights as provided for in the Bill of Rights.